Система Ag2S–GeS2 та кристалічна структура Ag2GeS3 - Олексеюк, И. Д.; Olekseyuk, I. D; Когут, Ю. М.; Kogut, Y. M; Федорчук, А. О.; Fedorchuk, A. O.; Пискач, Л. В.; Piskach, L. V.; Горгут, Г. П.; Gorgut, G. P.; Парасюк, О. В.; Parasyuk, O. V. (Волинський національний університет ім. Лесі Українки, 2010)
Диаграмма фазовых равновесий системы Ag2S–GeS2 была построена, используя результаты дифференциально-термического и рентгенофазового анализа. Подтверждено существование трёх соединений: Ag8GeS6, Ag10Ge3S11 и Ag2GeS3. Соединения Ag8GeS6 и Ag2GeS3 плавятся конгруэнтно при 1221 K и 922 K соответственно и являются диморфными. Для Ag10Ge3S11 характерен инкон- груэнтный тип образования при 1015 K. Рентгеновским методом порошка уточнена кристаллическая структура Ag2GeS3 (ПГ Cmc21, a = 1,17895(9) нм, b = 0,70751(5) нм, c = 0,63420(5) нм, RI = 0,0702) Phase equilibria diagram of the Ag2S–GeS2 system was investigated using the results of differential thermal analysis and X-ray diffraction. The existence of three compounds, Ag8GeS6, Ag10Ge3S11 and Ag2GeS3, was confirmed. Ag8GeS6 and Ag2GeS3 melt congruently at 1221 K and 922 K, respectively; these compounds are dimorphous. Ag10Ge3S11 is characterized by the incongruent type of formation at 1015 K. The crystal structure of Ag2GeS3 was refined using X-ray powder method (space group Cmc21, a = 1,17895(9) nm, b = 0,70751(5) nm, c = 0,63420(5) nm, RI = 0,0702).
The Ag2S– GeS2 System and the Crystal Structure of Ag2GeS3
Keywords: диаграмма фазовых равновесий; phase diagram, crystal structure; кристаллическая структура; crystal structure; халькогениды; chalcogenides